Director liability in insolvency and its vicinity - Van Zwieten, K (Oxford University Press, 2018)
Under English law, directors’ duties change in the vicinity of insolvency so as to require enhanced regard for creditors’ interests: that is the rule in West Mercia Safetywear v Dodd. This rule is conventionally analysed as a constraint on directors deploying assets in risky ventures in insolvency. However, a review of the case law shows that the rule performs a very different function: the regulation of payments to creditors in the lead-up to insolvency proceedings. On its own, the rule functions as an alternative to a preference action, providing recourse against the director who authorised the payment, rather than against the payee. Combined with accessory liability rules, the rule can also function as a substitute for a preference action, providing a different way of obtaining recourse against the payee. The first of these functions, however, raises a serious remedial problem—acknowledged by the courts—that appears ripe for consideration at an appellate level.